Design aspects of a large scale turbomolecular pump with active magnetic bearings. (August 2017) - Han, Bangcheng; Huang, Ziyuan; Le, Yun
Abstract: A large scale 5-axis magnetically levitated turbomolecular pump is designed and fabricated in this paper. The rotor is supported by two radial active magnetic bearings (AMBs) and an axial AMB, and driven by a high-speed brushless DC Motor with a ring permanent magnet. The considerations discussed are described by design of an actual magnetic levitation turbomolecular pump with rated high-speed vacuum pumping speed of 4100L/s and ultra-high vacuum of the order of 1.8 × 10 −7 Pa. The vacuum, stress, modal, and electromagnetic aspects are put equal weight in the design of a large scale turbomolecular pump supported by AMBs. The thermal assembly technology of the ring PM, sleeve, and shaft for the turbo rotor is proposed. Finally, the suggested design methodology for designing a large scale turbomolecular pump with AMBs is presented. Highlights: A large scale magnetically suspended turbomolecular pump (MSTMP) with holweck stage is widely developed for industrial application. The contribution of this paper is to put forward the design aspects of a large scale MSTMP. The considerations discussed are described by the design of a MSTMP with nominal pumping speed of 4100L/s and extremely high-vacuum of the order of 1.8 × 10 −7 Pa. The thermal assembly process of ring permanent magnet (PM), shaft, sleeve, and pump blade of rotor is proposed. A design methodology for designing a large scale MSTMP is suggested. The prototype is built, and the measured results verify the design respects proposed in this paper.